Minimum wages in Malaysia: concept and application - Aba Ibrahim, Nurhani; Said, Rusmawati (School of Economics, Faculty of Economics and Management, Universiti Kebangsaan Malaysia, 2013)
Whether to adopt a statutory minimum wage has been debated in Malaysia for a number of years, even after the enactment of the National Wages Consultative Act 2011. Despite the fact that the real labour productivity of Malaysia grew faster at 6.7 per cent between 2000 and 2008 compared to a mere 2.6 per cent increase in average wages, many employers still object to its implementation. This paper shed more light to the concept behind a statutory minimum wage policy and its application in the case of Malaysia. Its rationale and justification are reviewed and analysed. The dimensions considered determined the objectives, coverage and criteria for setting the minimum wages. The objectives of a minimum wages policy include addressing efficiency issues in labour markets, promoting productivity growth and reducing poverty or inequality. While the Malaysian government’s concern to improve the living standards of the poor and vulnerable is valid and merit serious attention, it is not the most appropriate instrument to address poverty and inequality. Besides that, many of the poor people are unemployed or employed in the informal sector where wages are not binding. Hence, the main justification for introducing and implementing a minimum wage policy in Malaysia would be to address inefficiencies in the labour markets that preclude competition, which can lead to the suppression of wages, especially the low-skilled and low-income workers. Comparisons are made among countries that have implemented the statutory minimum wages policy. This will help many to understand the common and different features that Malaysia has with them.